164. Reporting the High-resolution Structure of the Enterococcal Ribosome: A New Template for Antibiotic Discovery. (26th November 2018) - Jogl, Gerwald; Khayat, Reza; Murphy, Eileen; Kleffmann, Torsten; Singh, Kavindra; Murray, Barbara; Krause, Kurt
Abstract: Background: The ribosome is a rich target for antibiotic design and its structural secrets have been described at the atomic level over the past 2 decades. However, most bacterial ribosome structures come from nonpathogenic species of Archaea or thermophilic bacteria. To aid in the development of modern antibiotics against the enterococcus, we report the structure of the ribosome from Enterococcus faecalis at 3.5 Å resolution using cryo-electron microscopy. Methods: E. faecalis strain OG1 was grown in liquid culture, collected and lysed using a French press. 70S ribosomes were purified using centrifugation through a sucrose cushion followed by column chromatography and sucrose gradient centrifugation. 70S particles were diluted in buffer and applied to a holey carbon grid and using an FEI vitrobot were flash-frozen in liquid ethane. Data were collected on an FEI Titan Krios operating at 300 kV acceleration voltage. The particles classified into 6 distinct structures based on their composition. Completed maps were utilized for structure modelling using Coot and were then refined using real space refinement within Phenix. Results: High-quality maps of the 70S ribosome were obtained at up to 3.5 Å resolution in several distinct conformations. The 23S, 16S, and 5S RNA structures were almost completely built into maps with clear density. All but 2 ribosome proteins L25 and L33 have been placed in density. The A, P, and E sites were built into unambiguous density and found to be consistent with other bacterial structures. Notably, 1 EM density map contains an uncharged t-RNA molecule in the E site. The sites identified for current antibiotics are also well defined and interpretable. This 70S structural platform is suitable for structural analysis of antibiotic binding sites, especially for those antibiotics directed specifically against the enterococcal ribosome. Conclusion: For the first time, the structure of the ribosome from the important human pathogen Enterococcus faecalis has been determined. The maps were obtained at high resolution and found to be suitable for antibiotic design. It is anticipated that the continued determination of the structures of ribosomes from pathogens will aid in the discovery of new treatments for infectious diseases. Disclosures: All authors: No reported disclosures.